The influence of organisational context and practitioner attitudes on implementation of the carer support needs assessment tool (CSNAT) intervention. Issue 3 (1st September 2016) - Diffin, Janet; Ewing, Gail; Grande, Gunn
Abstract : Background: The Carer Support Needs Assessment Tool (CSNAT) intervention identifies and addresses family carer support needs towards end of life. 1–3 A paucity of studies has investigated how to successfully implement evidence based interventions within palliative care. Aim: Investigate how staff attitudes and organisational context affect implementation of the CSNAT intervention in palliative care. Methods: 36 UK palliative care services participated. Staff surveys measured attitudes and context prior to, and six months after the implementation began including (i) a questionnaire assessing staff attitudes to the CSNAT; (ii) The Alberta Context Tool (ACT) assessing organisational context. Data on use of the CSNAT intervention were collected over six months; services were classified as 'high' or 'low' adopters on this basis. Relationships between service characteristics, aggregate data on staff attitudes and organisational context, and level of adoption were analysed. Results: 157/462 surveys were returned at baseline and 69/462 at six months. Level of adoption depended on service type. 'High' adopters had a higher ratio of intervention 'champions' to total staff numbers and higher scores for ACT 'informal interactions' (e.g. more discussions with colleagues about patient care), compared to 'low' adopters. Both groups had similarly positive attitudes to the CSNAT intervention pre-implementation. By six months attitudes for 'low' adopters were significantly more negative, but remained similar or improved for 'high' adopters. Conclusions: Ensuring successful implementation of complex interventions within palliative care requires consideration of the organisational context, service type, strategies for maintaining positive staff attitudes over time, and the use of intervention 'champions'. References: Ewing G, Brundle C, Payne S, Grande G. The Carer Support Needs Assessment Tool (CSNAT) for use in palliative and end-of-life care at home: A validation study. J Pain Symptom Manage 2013;46 (3):395–405 Ewing G, Grande G. Development of a Carer Support Needs Assessment Tool (CSNAT) for end-of-life care practice at home: a qualitative study. Palliat Med 2013;27 (3):244–256 Ewing G, Austin L, Diffin J, Grande G. The Carer Support Needs Assessment Tool: A person centred approach to carer assessment and support. Br J Community Nurs 2015;20 (12):580–584